Cost-effectiveness of a patient-centred approach to managing multimorbidity in primary care: a pragmatic cluster randomised controlled trial. Issue 1 (19th January 2020) - Thorn, Joanna; Man, Mei-See; Chaplin, Katherine; Bower, Peter; Brookes, Sara; Gaunt, Daisy; Fitzpatrick, Bridie; Gardner, Caroline; Guthrie, Bruce; Hollinghurst, Sandra; Lee, Victoria; Mercer, Stewart W; et al.
Abstract : Objective: Patients with multiple chronic health conditions are often managed in a disjointed fashion in primary care, with annual review clinic appointments offered separately for each condition. This study aimed to determine the cost-effectiveness of the 3D intervention, which was developed to improve the system of care. Design: Economic evaluation conducted alongside a pragmatic cluster-randomised trial. Setting: General practices in three centres in England and Scotland. Participants: 797 adults with three or more chronic conditions were randomised to the 3D intervention, while 749 participants were randomised to receive usual care. Intervention: The 3D approach: comprehensive 6-monthly general practitioner consultations, supported by medication reviews and nurse appointments. Primary and secondary outcome measures: The primary economic evaluation assessed the cost per quality-adjusted life year (QALY) gained from the perspective of the National Health Service (NHS) and personal social services (PSS). Costs were related to changes in a range of secondary outcomes (QALYs accrued by both participants and carers, and deaths) in a cost–consequences analysis from the perspectives of the NHS/PSS, patients/carers and productivity losses. Results: Very small increases were found in both QALYs (adjusted mean difference 0.007 (−0.009 to 0.023)) and costs (adjusted mean difference £126 (£−739 to £991)) in the intervention arm compared with usual care after 15 months. The incremental cost-effectiveness ratio was £18 499, with a 50.8% chance of being cost-effective at a willingness-to-pay threshold of £20 000 per QALY (55.8% at £30 000 per QALY). Conclusions: The small differences in costs and outcomes were consistent with chance, and the uncertainty was substantial; therefore, the evidence for the cost-effectiveness of the 3D approach from the NHS/PSS perspective should be considered equivocal. Trial registration number: ISCRTN06180958